Robust Results From Climate Model Simulations of Geoengineering: GeoMIP 2013; Potsdam, Germany, 15–16 April 2013. (13th August 2013) - Kravitz, Ben; Robock, Alan; Irvine, Peter
Abstract: Solar geoengineering has been proposed as a temporary means of alleviating some of the consequences of anthropogenic greenhouse gas emissions. Single‐model studies characterizing the resulting climate effects often used different greenhouse gas concentration profiles and different amounts of geoengineering, making intercomparison difficult. The Geoengineering Model Intercomparison Project (GeoMIP) created a framework of four core simulations, designed to reveal robust features and key uncertainties of climate model responses to geoengineering (B. Kravitz et al., The Geoengineering Model Intercomparison Project (GeoMIP), Atmospheric Science Letters, 12 (2), 162–167, doi:10.1002/asl.316, 2011). These experiments simulate solar geoengineering via uniform solar reduction or creation of stratospheric sulfate aerosol layers using state‐of‐the‐art climate models.